The natural history of Annonaceae (2012)
This special issue of Botanical Journal of the Linnean Society focuses on the systematics and evolution of Annonaceae. Ever since the start of the standardized use of plant family names, with the publication of Genera plantarum by de Jussieu (1789), Annonaceae have been an easily identifiable entity. The numerous cultivated species have provided further recognition of the family for centuries. On a local scale, many species are used for their fleshy, edible fruits and others for aromatic, spicy, medicinal or mechanic properties. Perhaps most pleasing, and more widely known, are the essential oil of the Asian species ylang?ylang (Cananga odorata (Lam.) Hook.f. & Thomson) and the edible fruits of several species of the Neotropical genus Annona L. Halfway through the 17th century, Annona spp. had already been widely distributed across the Atlantic and were among the popular fruits cultivated in the first Dutch settlement at the Cape of Good Hope. Trees of C.?odorata had probably been widely planted in Polynesia and Micronesia before the species was further disseminated to Africa and the New World in colonial times.